An Exploration of Interorganizational Arrangements That Support School Improvement - Cates, Carolyn S.; Far West Lab. for Educational Research and Development, San Francisco, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1981)
Researchers surveyed 13 counties in the Greater San Francisco Bay Area (California) to identify and classify educational agencies' cooperative, interorganizational arrangements (IOAs) for school improvement and to describe the characteristics of different types of IOAs. Data were collected from interviews, directories, and documents. Five IOA characteristics were studied: their history, environmental context, structure, operations, and outputs. The survey identified 103 IOAs in the Bay Area and revealed that 67 percent of the 409 educational agencies in the region, including all 231 school districts, were involved in one or more IOAs. The researchers developed a classification system based on two dimensions: the IOA's legal status (whether mandated by outside agencies, enabled or sponsored by outside agencies, or "freestanding," meaning supported chiefly by member organizations), and the school improvement's legal status (mandated, enabled, or freestanding). Analysis based on this classification system showed, among other things, that most IOAs relied on external requirements or resources and that IOA characteristics include both tight and loose coupling. The findings bear a number of implications for research and policy on educational collaboration and school improvement. An appendix provides extensive descriptions of the characteristics of types of IOAs. (Author/RW)
Sponsoring Agency: National Inst. of Education (ED), Washington, DC.
Contract Number: 400-80-0103.
ERIC Note: For related documents, see EA 014 745-746 and EA 014 748-749.
Educational level discussed: Elementary Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Classification; Community Surveys; Cooperative Programs; Educational Cooperation; Educational Improvement; Educational Legislation; Elementary Secondary Education; Government School Relationship; Institutional Characteristics; Institutional Cooperation; Legal Responsibility; School Districts; Tables (Data); California (San Francisco Bay Area) -- Legal Status; Reports, Research